The groundnut crop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The groundout crop: a scientific basis for improvement edited by J Smartt 1994 733pp ISBN 0412 40820 1 Chapman & Hall, 2-6 Boundary Row, London SE1 8HN, UK